Extending the Technology Acceptance Model to Explore Students’ Intention to Use an Online Education Platform at a University in China - Zhou, Liqiu; Xue, Sijia; Li, Ruiqian (SAGE open, 2022)
While online education has been increasingly adopted in different educational systems across the world, it is still a recent phenomenon in developing countries such as China. Various factors could affect learners’ adoption of technology, including their online learning. In this study, we took the Technology Acceptance Model as the theoretical framework and extended the Model by including extra external variables and one perceived variable to explore factors influencing learners’ intention to use an online education platform. A total of 276 college students from a university in mainland China participated in the study. Results showed that 9 of the 12 hypotheses proposed were supported. External variables such as Online Course Design, Perceived System Quality, and Perceived Enjoyment, along with an extra perceived variable (Perceived Interaction) have been identified as effective predictors of learners’ intention to use the education platform. Implications of the findings are discussed and suggestions for future research are provided.